819 INSTITUTIONAL VARIATION IN THE ORGANIZATION OF CLINICAL PATHWAYS IN ESOPHAGOGASTRIC CANCER, A MIXED METHOD MULTIPLE CASE STUDY. (17th September 2021) - Luijten, Josianne; Vissers, Pauline; Verhoeven, Rob; Nieuwenhuijzen, Grard; Westerman, Marjan
Abstract:  : The probability of undergoing treatment with curative intent according to the hospital of diagnosis has been shown to vary considerately for esophagogastric cancer and was related to survival. However, little is known which factors attribute to this variation. In this study we aimed to gain in-depth understanding of the organization of clinical pathways and in particular factors and processes determining the organization of healthcare for esophagogastric cancer patients. Methods: A mixed method study design consisting of quantitative and qualitative data was conducted. Quantitative data was gathered by the Netherlands cancer registry (e.g., outpatient clinic consultations and performed diagnostics). A thematic content analyses of the current sub-study focused on clinician's perspectives using semi-structured interviews (n = 30), and observations of outpatient clinic consults (n = 26) as well as multidisciplinary team meetings (n = 16) in eight hospitals. Results: Quantitative analyses showed that surgeons were more often consulted in hospitals with a high probability whereas geriatricians were more often consulted in hospitals with a low probability of receiving treatment with curative intent. Qualitative analyses showed that the organization of clinical pathways were analyzed according to three levels: regional, local and patient level. Hospitals differed regarding triage, patients discussed during an multidisciplinary team meeting, the revision of radiological images, and restaging after neoadjuvant treatment. Furthermore, assessment of patients physical and cognitive condition by fitness tests, pre-habilitation and/or geriatric assessment differed significantly. Conclusion: Specific parts of the clinical pathways differed significantly between hospitals such as the consultation of a geriatrician and pre-habilitation. These results might provide implications for further research in order to optimize clinical pathways.